Lipid Profile, PCSK9, ANGPTL3 and Lipoprotein (a) Levels in Men Diagnosed With Localized High‐Grade Prostate Cancer and Men At‐Risk of Prostate Cancer - Ann‐Charlotte Bergeron; Emilie Wong‐Chong; France‐Hélène Joncas; Chloé Castonguay; Frédéric Calon; Nabil G. Seidah; Jonatan Blais; Karine Robitaille; Alain Bergeron; Vincent Fradet; Anne Gangloff (Cancer Medicine)
ABSTRACT Background Some cancers have been found to require abundant supplies of lipids for their development. One example is prostate cancer (PCa). To date, lipid‐modifying factors, such as proprotein convertase subtilisin/kexin type 9 (PCSK9), angiopoietin‐like 3 protein (ANGPTL3), and lipoprotein(a) or Lp(a), have not been reported in men with PCa. The present study aimed to verify whether plasma levels of these lipid‐related proteins vary in men with PCa compared to at‐risk but cancer‐free men. Methods Plasma samples from 35 men with locally advanced PCa Gleason 8 and 9 versus 35 men at risk of PCa were selected as cases and controls. Blood samples were paired according to age and BMI. Apolipoprotein B100 (Apo B), Lp(a), and lipid profiles were measured on an analytical platform (Roche Cobas). PCSK9 and ANGPTL3 levels were determined by ELISA. Results No significant change in lipids and related factors levels was observed between men with localized PCa Gleason 8 or 9 and matched controls. A correlation between ANGPTL3 and HDL levels was only confirmed in controls (ρ = 0.54, p = 0.0009). PCSK9 was inversely associated with PSA levels in the entire cohort (ρ = −0.31, p < 0.01), suggesting that factors influencing PCSK9 could also influence PSA levels. In controls only, PSA levels were correlated with LDL, Apo B, non‐HDL, total cholesterol, and triglycerides (all ρ coefficients ≥ 0.35, all p‐values < 0.05). PCSK9 was correlated to LDL in PCa men, but the relationship was unexpectedly found to be inverse. Conclusions In this observational study, lipid profiles, PCSK9, ANGPTL3, and Lp(a) levels did not change in men diagnosed with locally advanced Gleason 8 or 9 PCa compared to at‐risk but cancer‐free men. The present data suggest a complex interplay between PCSK9, PSA, and the lipid profile in localized PCa.